2014
DOI: 10.1186/s12934-014-0119-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving itaconic acid production through genetic engineering of an industrial Aspergillus terreus strain

Abstract: BackgroundItaconic acid, which has been declared to be one of the most promising and flexible building blocks, is currently used as monomer or co-monomer in the polymer industry, and produced commercially by Aspergillus terreus. However, the production level of itaconic acid hasn’t been improved in the past 40 years, and mutagenesis is still the main strategy to improve itaconate productivity. The genetic engineering approach hasn’t been applied in industrial A. terreus strains to increase itaconic acid produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 42 publications
(72 reference statements)
3
34
0
Order By: Relevance
“…By insertion of the modified A. niger pfKA genes into A. terreus strain, specific productivities and final yields of IA were increased in comparison to the parent strain. Huang et al [33] overexpressed cadA and mfsA (major facilitator superfamily transporter) genes in A. terreus and obtained enhanced IA production level by 9.4 and 5.1% in shake flasks, respectively, in comparison to wild type. Geiser et al [23] reported that overexpression of a pathway-specific transcription factor (Ria1) or a mitochondrial tricarboxylic acid transporter (Mtt1) in U. maydis resulted in a 2-fold increase in IA yield.…”
Section: Recombinant Microorganisms For Production Of Itaconic Acidmentioning
confidence: 97%
See 1 more Smart Citation
“…By insertion of the modified A. niger pfKA genes into A. terreus strain, specific productivities and final yields of IA were increased in comparison to the parent strain. Huang et al [33] overexpressed cadA and mfsA (major facilitator superfamily transporter) genes in A. terreus and obtained enhanced IA production level by 9.4 and 5.1% in shake flasks, respectively, in comparison to wild type. Geiser et al [23] reported that overexpression of a pathway-specific transcription factor (Ria1) or a mitochondrial tricarboxylic acid transporter (Mtt1) in U. maydis resulted in a 2-fold increase in IA yield.…”
Section: Recombinant Microorganisms For Production Of Itaconic Acidmentioning
confidence: 97%
“…cis-Aconitate is transported back into the cytosol with the help of mitochondrial tricarboxylic acid transporter and serves as a precursor for IA production by decarboxylation by the action of cis-aconitic acid decarboxylase (CAD, EC 4.1.16, Fig. 1) [10,33,34,83]. Bentley and Thiessen [3,4] successfully decarboxylated cis-aconitic acid into IA using crude CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Although the most significant progress in improving itaconic acid production is made by classical process optimization techniques until now (Hevekerl et al 2014), the construction of mutant strains by genetic engineering is also promising for improving the itaconic acid production. For example, overexpression of CAD in A. terreus LYT10 enhanced the itaconic acid production level by nearly 10 % in shake flasks, and the production stage was shortened by around 4 h at the pilot scale (35 m 3 fermentor) (Huang et al 2014b). We do believe that the combination of classical process optimization and genetic engineering will make greater progress in improving itaconic acid production.…”
Section: Discussionmentioning
confidence: 99%
“…In an effect to improve the application potential of itaconic acid, a great deal of research related to itaconic acid biosynthesis (Bonnarme et al 1995;Jaklitsch et al 1991;Li et al 2011) and its regulation mechanism (Huang et al 2014b;Lin et al 2004;Reddy and Singh 2002;Tevz et al 2010) have been carried out to improve the production efficiency of itaconic acid. In addition to enhancing the biosynthesis pathway, disrupting or weakening the degradation pathway by metabolic engineering is also an effective strategy to promote the accumulation of target products.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, various studies, including those employing optimization of culture conditions and the improvement and development of hosts, have tried to improve production yield. Despite these efforts, there has been no improvement in the maximum productivity of IA (86.2 g/L) in the past 40 years (Huang et al, 2014b).…”
Section: Introductionmentioning
confidence: 97%